2007
DOI: 10.1139/b07-015
|View full text |Cite
|
Sign up to set email alerts
|

An altered root exudation pattern through mycorrhization affecting microconidia germination of the highly specialized tomato pathogen Fusarium oxysporum f. sp. lycopersici (Fol) is not tomato specific but also occurs in Fol nonhost plants

Abstract: The effect of root exudates from plants colonized or noncolonized by the arbuscular mycorrhizal fungus Glomus mosseae on microconidia germination of Fusarium oxysporum f. sp. lycopersici (Fol) was studied. Root exudates from the Fol-host tomato and root exudates from Fol nonhost plants were tested. Root exudates from all tested plants stimulated microconidia germination. Mycorrhization increased the stimulatory effect exhibited by the root exudates from the Fol host tomato and from all Fol nonhost plants, show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…This may be due to high variation in microconidial germination in the water control reported in previous studies (Scheffknecht et al 2006(Scheffknecht et al , 2007. In all our studies with Fol 007 (Steinkellner et al 2005;Scheffknecht et al 2006Scheffknecht et al , 2007 a highly standardised experimental set-up was used for fungal cultures of the same age, the same spore preparation and concentration, the same type of microplates, the same water treatment (distilled and autoclaved), the same growth chamber and temperature for the germination assay, the water control values varied. Thus, the observed variation must be attributed to the biological variation of the fungal material which is not uncommon for living organisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be due to high variation in microconidial germination in the water control reported in previous studies (Scheffknecht et al 2006(Scheffknecht et al , 2007. In all our studies with Fol 007 (Steinkellner et al 2005;Scheffknecht et al 2006Scheffknecht et al , 2007 a highly standardised experimental set-up was used for fungal cultures of the same age, the same spore preparation and concentration, the same type of microplates, the same water treatment (distilled and autoclaved), the same growth chamber and temperature for the germination assay, the water control values varied. Thus, the observed variation must be attributed to the biological variation of the fungal material which is not uncommon for living organisms.…”
Section: Discussionmentioning
confidence: 99%
“…However, recently, it has been shown that fungi in the rhizosphere can alter the exudation pattern of plant roots and thus can affect microconidial germination of F. oxysporum. Root exudates of tomato, barley, maize, papaya, cucumber and many more plants, colonized by the arbuscular-mycorrhizal fungus Glomus mosseae, exhibited a different effect on the microconidial germination of Fol 007 than root exudates from non-mycorrhizal plants (Scheffknecht et al 2006(Scheffknecht et al , 2007. This indicates that alterations of the root exudation pattern due to fungi are fungus-specific.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, mycorrhizal colonization was shown to modify the exudates of tomato roots [52], and the stimulatory effect of root exudates from many plant species to the germination of conidia of Fusarium oxysporum f. sp. lycopersici, a tomato root pathogen [226].…”
Section: Root Exudation the Ecological Driver Of Microbial Communitimentioning
confidence: 99%
“…There are a number of reports on root exudates and AMF (see recent reviews by Jones et al 2004;Nagahashi and Douds 2005;Vierheilig and Bago 2005), and more and more data are accumulated that exudates of mycorrhizal plants affect bacteria (Sood 2003), fungi (Norman and Hooker 2000;Lioussanne et al 2003;Scheffknecht et al 2006Scheffknecht et al , 2007 and nematodes (Ryan and Jones 2004) differently then exudates from nonmycorrhizal plants.…”
Section: Biochemical and Molecular Changes In Mycorrhizal Plants Thatmentioning
confidence: 99%
“…Looking at the chemotactic response root exudates collected from non-mycorrhizal tomato roots exhibited a higher attracting effect on zoospores of P. parasitica (Lioussanne et al 2003), whereas in the case of the two plant-growthpromoting bacteria A. chroococum and P. fluorescens, root exudates from mycorrhizal tomato plants showed a higher attractional effect (Sood 2003). Most recently it was reported that root exudates from mycorrhizal plants show an altered effect on microconidia germination of F. oxysporum compared to root exudates from nonmycorrhizal plants (Scheffknecht et al 2006(Scheffknecht et al , 2007.…”
Section: Alterations Of the Root Exudation Patternmentioning
confidence: 99%